Perspektif Gender Petani Perempuan Lampung - Handayani, Dwi Wahyu (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), Sekolah Tinggi Ilmu Sosial dan Ilmu Politik (STISIPOL) Candradimuka, 2025)
The political economy approach to the agricultural sector has thus far neglected to consider the power relations that underpin gender inequality, instead focusing on class relations. The agricultural sector in Lampung plays a crucial role in the national food supply, with women farmers representing approximately 12.55% of the workforce. This research was conducted in four districts in Lampung Province, based on data indicating the highest concentration of women farmers, namely Pringsewu, South Lampung, East Lampung, and Central Lampung. This study aims to examine the perspectives of women farmers in Lampung on the management of agricultural land. The findings of the research indicate that women farmers' perspectives on resource aspects, including ownership of farmland assets, division of labor, decision-making, and agricultural institutions, are that these are managed more effectively when under the authority of men. This perspective causes women to feel that they are merely assisting men, rather than being fully involved in land management, and that the agricultural sector is a male-dominated domain. In the agency dimension, women farmers are demonstrating their agency by attempting to move away from domestic affairs and increasing their understanding of cooperation in land management and household economic responsibilities. In the achievement dimension, the women's agency is reflected in the transformation of women's involvement in land management, which is a consequence of male dominance in the agricultural sector. Keywords: gender analysis, perspective of women farmers, resources, agency, and achievement.